INVESTOR BEHAVIOR IN DETERMINING INVESTMENT ON REAL ASSET - yuniningsih yuniningsih; Muhamad Taufiq (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
Behavior in determining investment is influenced by factors from the fundamental side or individual psychology. This study aims to determine how psychological factors influence investor behavior in determining future investments. This research is a field experimental study using questionnaire data. The variables used in investment decision making include loss aversion, regret aversion and illusion of control bias with 15 total indicators. The sample is an investor in the real asset field and the data is processed using the Structural Equation Model (SEM) with the AMOS program. The results showed that psychological factors both loss aversion and illusion of control bias had a significant effect on investment decisions in a positive direction. While regret aversion has a significant effect with negative direction with investment decisions. Novelty in this study, that psychological factors in behavior finance not only affect securities investors but also real asset investors.